Biphasic components of sarcomatoid clear cell renal cell carcinomas are molecularly similar to each other, but distinct from, non‐sarcomatoid renal carcinomas. (7th July 2015) - Sircar, Kanishka; Yoo, Suk‐Young; Majewski, Tadeusz; Wani, Khalida; Patel, Lalit R.; Voicu, Horatiu; Torres‐Garcia, Wandaliz; Verhaak, Roel G. W.; Tannir, Nizar; Karam, Jose A.; Jonasch, Eric; Wood, Christopher G.; et al.
Abstract: Sarcomatoid transformation, wherein an epithelioid carcinomatous tumour component coexists with a sarcomatoid histology, is a predictor of poor prognosis in clear cell renal cell carcinoma. Our understanding of sarcomatoid change has been hindered by the lack of molecular examination. Thus, we sought to characterize molecularly the biphasic epithelioid and sarcomatoid components of sarcomatoid clear cell renal cell carcinoma and compare them to non‐sarcomatoid clear cell renal cell carcinoma. We examined the transcriptome of the epithelioid and sarcomatoid components of advanced stage sarcomatoid clear cell renal cell carcinoma ( n =43) and non‐sarcomatoid clear cell renal cell carcinoma ( n =37) from independent discovery and validation cohorts using the cDNA microarray and RNA‐seq platforms. We analyzed DNA copy number profiles, generated using SNP arrays, from patients with sarcomatoid clear cell renal cell carcinoma ( n =10) and advanced non‐sarcomatoid clear cell renal cell carcinoma ( n =155). The epithelioid and sarcomatoid components of sarcomatoid clear cell renal cell carcinoma had similar gene expression and DNA copy number signatures that were, however, distinct from those of high‐grade, high‐stage non‐sarcomatoid clear cell renal cell carcinoma. Prognostic clear cell renal cell carcinoma gene expression profiles were shared by the biphasic components of sarcomatoid clear cell renal cell carcinoma and the sarcomatoid component showed a partial epithelial‐to‐mesenchymal transition signature. Our genome‐scale microarray‐based transcript data were validated in an independent set of sarcomatoid and non‐sarcomatoid clear cell renal cell carcinomas using RNA‐seq. Sarcomatoid clear cell renal cell carcinoma is molecularly distinct from non‐sarcomatoid clear cell renal cell carcinoma, with its genetic programming largely shared by its biphasic morphological components. These data explain why a low percentage of sarcomatoid histology augurs a poor prognosis; suggest the need to modify the pathological grading system and introduce the potential for candidate biomarkers to detect sarcomatoid change preoperatively without specifically sampling the histological sarcomatoid component.